Hubungan Kesejahteraan Seksual dengan Kesehatan Psikologi pada Ibu Hamil di Wilayah Kelurahan Kuningan Bandarharjo - Widya Ayu Christiani; Hernandia Distinarista; Tutik Rahayu (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
For a woman, pregnancy is a phase of life that is full of significant physical, emotional, and psychological changes. Pregnancy also affects psychological and emotional aspects, which are often associated with the psychological health of the mother. Sexuality is an important part of human life, and is influenced by hormonal, physical, and psychological changes during pregnancy, but is often overlooked in research on maternal well-being. To find out the relationship between sexual well-being and psychological health in pregnant women in the Kuningan Bandarharjo sub-district area. Quantitative cross-sectional, the sample used purposive sampling of 77 respondents. The correlation test used is the contingency coefficient. Most respondents are 25-30 years old. The results of the Somers test